Fixed-time continuous stochastic synchronisation of two-layer dynamical networks. Issue 2 (25th January 2020) - Tan, Fei; Zhou, Lili; Yu, Fei; Lu, Junwei
Abstract : This paper sheds light on the problem of fixed-time continuous stochastic outer synchronisation for two-layer networks with different topologies, which can be undirected or directed. With the Lyapunov stability theory, several sufficient conditions are obtained. To guarantee the fixed-time continuous stochastic synchronisation of two-layer dynamic networks, the continuous chattering-free feedback controllers are designed. Finally, simulation examples are provided to illustrate the effectiveness of our results.